Frequency of sleep disorders in rural workers - Sousa, Milena Nunes Alves de; Silva Oliveira, Cíntia; Formiga, Marcus Winícius Mendes; Araújo, Neuza Caroline Suassuna (Brazilian Journal of Production Engineering, 2021)
Context: The majority of rural workers have a low quality of life because they work tirelessly for very low pay or suffer from the instability of unemployment due to the seasonality of the activity. Objective: Detect, select and synthesize the relevant evidence in national and international literature related to the development of sleep disorders in rural workers. Methods: Systematic review carried out in the Medical Literature and Retrivial System Online (PUBMED) databases, The Scientific Electronic Library Online (SCIELO) and Virtual Health Library (VHL), with publication between the years 2010 to 2020, in Portuguese and English; in the Science Direct (SD) database, research articles from the last five years, from 2015 to 2020, were selected; both took into account the assessment of sleep disorders in rural workers. From the guiding question, was constructed the material was selected based on the combinations of the descriptors: "Rural workers" OR farmers AND "sleep disorders" - employed at PUBMED and SD - and "Rural workers" OR farmers AND "sleep disorders" - applied in SCIELO and the VHL. After the initial identification of the articles, reading was carried out in pairs and selection according to the eligibility criteria. Results: Eight articles were selected. Most studies were a Cohort Study. It is very common for rural workers to experience sleep disorders, as well as anxiety and depression, especially those who do not have a fixed job, depending on the harvests. Conclusion: The development of sleep disorders in rural workers has a multifactorial cause and is determinant for other diseases, requiring interventions in the field of occupational health.
Keywords: Agriculture. Worker categories. Sleep disorders.